International Normalized Ratio as a Screening Test for Assessment of Anticoagulant Activity for Patients Treated With Rivaroxaban or Apixaban: A Pilot Study - Ofek, Fanny; Barchel, Dana; Perets, Nofar; Ziv-Baran, Tomer; Mahajna, Ahmad; Filipovich-Rimon, Talia; Garach-Jehoshua, Osnat; Berlin, Maya; Berkovitch, Matitiahu (Frontiers in Pharmacology, 2019)
Introduction In patients treated with direct oral anti activated factor X (anti-FXa) anticoagulants such as apixaban and rivaroxaban, there are several emergency and non-emergency conditions in which anticoagulation activity should be measured. The validity of the common global clotting tests, Prothrombin time and International Normalized Ratio (PT/INR) for determination of blood levels of these drugs has been widely investigated. As the anticoagulation activity evaluation "calibrated anti-FXa" of these drugs, is relatively more expensive and less available, we aimed to build a prediction model for anticoagulation activity assessment based on INR values. Methods and findings 160 samples from 80 hospitalized patients treated with apixaban or rivaroxaban, were tested using PT/INR, and Anti-FXa chromogenic assay. Two blood samples, trough and peak, were collected from each subject. Participants were randomly divided into two equal groups. One group (n=40) was used to build the model, which was validated by the second group (n=40). There was a strong correlation between anti-FXa concentrations and INR in rivaroxaban treated patients (r = 0.899, p<0.001). Therefore, we were able to build a formula for rivaroxaban patient group which reliably represent the relationship between these two parameters. The correlation in apixaban treated patients was less predictive (r = 0.798, p<0.001) and the formula suggested could not be validated. Conclusions In our study, we developed a formula that estimates the anticoagulant activity of rivaroxaban by obtaining INR values. Where anti-FXa assay is unavailable our proposed formula may be considered as a screening test for rivaroxaban.